SPIRITUAL INTELLIGENCE AS SCHEMA FOR DECISION MAKING - THE UNTAPPED FRONTIER - I Alam, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The bedrock of all major religious beliefs has been that ‘Man is a spiritual being, in search of the ultimate knowledge’. However, it is only recently that this aspect has been investigated from a scientific and analytical perspective and how it influences an individual’s personality construct. The paper analyses the transformative potential of Spiritual Intelligence (SI) and effect on the decision-making ability of an individual and how it affects the cognitive capability of the human mind. The research extends the SI idea as a schemain order to suggest that it works both to restrict choices and to perceive cognitive information. This model provides a more detailed picture of the SI’s impact and focuses the hypothesis on current human cognition theory. The paper, based on conceptual based theoretical evidence,proposes an Analytical Framework, which has been verified by quantitative data analysis on individuals in various leadership roles in the field of information technology. “Our culturesencourage us to learn both ‘spiritual’ and ‘worldly’ knowledge. If one learns spirituality, then worldly knowledge will become founded on spirituality.”